Effect of interlayer coupling on the reversal process of differential dual spin valves - Sekhar, Murapaka Chandra (2013)
Differential dual spin valve (DDSV) is a potential read sensor for ultrahigh density magnetic recording. Recently, it has been found that self-biased DDSVs in which the two free layers (FLs) align in flux closure configuration could potentially remove permanent hard bias. In the present work, we have carried out a systematic study of the effect of the interlayer coupling through gap layer on the reversal process of a self-biased DDSV. From the uniform field response of the DDSV, it was found that the competition among magnetostatic coupling, interlayer coupling and the shape anisotropy of the FLs gives rise to distinctive reversal behaviors, and the magnetostatic coupling could not be perfectly compensated by the interlayer exchange coupling. The down track response of the DDSV reveals that interlayer coupling could play a dominant role on the performance of the DDSV.